CD47 blockade reduces ischemia/reperfusion injury and improves survival in a rat liver transplantation model. Issue 4 (29th January 2015) - Xiao, Zhen‐Yu; Banan, Babak; Jia, Jianluo; Manning, Pamela T.; Hiebsch, Ronald R.; Gunasekaran, Muthukumar; Upadhya, Gundumi A.; Frazier, William A.; Mohanakumar, Thalachallour; Lin, Yiing; Chapman, William C.
<x xml:space="preserve">Abstract</x> Orthotopic liver transplantation (OLT) remains the standard treatment option for nonresponsive liver failure. Because ischemia/reperfusion injury (IRI) is an important impediment to the success of OLT, new therapeutic strategies are needed to reduce IRI. We investigated whether blocking the CD47/thrombospondin‐1 inhibitory action on nitric oxide signaling with a monoclonal antibody specific to CD47 (CD47mAb400) would reduce IRI in liver grafts. Syngeneic OLT was performed with Lewis rats. Control immunoglobulin G or CD47mAb400 was administered to the donor organ at procurement or to both the organ and the recipient at the time of transplant. Serum transaminases, histological changes of the liver, and animal survival were assessed. Oxidative stress, inflammatory responses, and hepatocellular damage were also quantified. A significant survival benefit was not achieved when CD47mAb400 was administered to the donor alone. However, CD47mAb400 administration to both the donor and the recipient increased animal survival afterward. The CD47mAb400‐treated group showed lower serum transaminases, bilirubin, oxidative stress, terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate nick‐end labeling staining, caspase‐3 activity, and proinflammatory cytokine expression of tumor necrosis factor α, interleukin‐1β, and interleukin‐6. Thus, CD47 blockade with CD47mAb400 administered both to the donor and the recipient reduced liver graft IRI in a rat liver transplantation model. This may translate to decreased liver dysfunction and increased survival of liver transplant recipients. Liver Transpl 21:468–477, 2015. © 2015 AASLD.